Development and field evaluation of a seedling polybag soil filling machine for oil palm nursery - Hassan, Haslina; Yahya, Azmi; El Pebrian, Darius; Mat Su, Ahmad Suhaizi (Malaysian Palm Oil Board, 2023)
The need to produce high-quality seedlings with adequate quantity has placed a burden on nursery operators, who often require substantial capital and labour with limited daily production capability. The goal of this project was to develop a seedling polybag soil filling machine and evaluate its performance in a simulated oil palm nursery, emphasising small polybag production. The 51 kW diesel engine of a universal, multipurpose 4WD (four-wheel drive) prime mover was utilised to transmit the power to the mixer and auger of the machine system. The recorded average production capacity was 198 bags man hr–1, which was 24.24% higher than the conventional practice of 150 bags man hr–1. The final weight was within the limit (<5%) for both small and large polybags. The production capacity of the machine was moderately improved, despite an increase of approximately 53% in total costs per polybag over the conventional practice. Generally, the machine can be deployed in seedling production of the oil palm nursery stage to fill the polybags with suitable planting media selection.